Mechanical Cues, E-Cadherin Expression and Cell “Sociality” Are Crucial Crossroads in Determining Pancreatic Ductal Adenocarcinoma Cells Behavior - Francesca Bianchi; Michele Sommariva; Laura Brigida Cornaghi; Luca Denti; Ambra Nava; Francesca Arnaboldi; Claudia Moscheni; Nicoletta Gagliano (Cells, 2022)
E-cadherin, an epithelial-to-mesenchymal transition (EMT) marker, is coupled to actin cytoskeleton and distributes cell forces acting on cells. Since YAP transduces mechanical signals involving actin cytoskeleton, we aimed to investigate the relationship between YAP and mechanical cues in pancreatic ductal adenocarcinoma (PDAC) cell lines, characterized by different EMT-related phenotypes, cultured in 2D monolayers and 3D spheroids. We observed that the YAP/p-YAP ratio was reduced in HPAC and MIA PaCa-2 cell lines and remained unchanged in BxPC-3 cells when cultured in a 3D setting. CTGF and CYR61 gene expression were down-regulated in all PDAC 3D compared to 2D cultures, without any significant effect following actin cytoskeleton inhibition by Cytochalasin B (CyB) treatment. Moreover, LATS1 mRNA, indicating the activation of the Hippo pathway, was not influenced by CyB and differed in all PDAC cell lines having different EMT-related phenotype but a similar pattern of CTGF and CYR61 expression. Although the role of YAP modulation in response to mechanical cues in cancer cells remains to be completely elucidated, our results suggest that cell arrangement and phenotype can determine variable outcomes to mechanical stimuli in PDAC cells. Moreover, it is possible to speculate that YAP and Hippo pathways may act as parallel and not exclusive inputs that, converging at some points, may impact cell behavior.